Review and Clinical Perspectives for the Use of Infliximab in Ulcerative Colitis. (2008) - Panaccione, Remo; Fedorak, Richard N; Aumais, Guy; Bernard, Edmond-Jean; Bernstein, Charles N; Bitton, Alain; Croitoru, Ken; Dieleman, Levinus A; Enns, Robert; Feagan, Brian G; Franchimont, Denis; Greenberg, Gordon R; et al.
Abstract : Infliximab is a chimeric, monoclonal anti-tumour necrosis factor-alpha antibody. It has been previously demonstrated to be an effective treatment for patients with Crohn's disease who do not achieve the desired response with conventional treatments. Although the etiology of ulcerative colitis (UC) differs from that of Crohn's disease, randomized controlled trials have demonstrated that infliximab is also beneficial for the treatment of moderate to severe UC in patients who are either intolerant of or refractory to immunosuppressant agents or steroids, or those who are steroid-dependent. A review of the literature is followed by practical recommendations regarding infliximab that address the needs of clinicians and UC patients. Where there is a lack of evidence-based information, the expert panel provides its combined opinion derived from the members' clinical experiences.